Five-Year Cancer Epidemiology at the National Referral Hospital: Hospital-Based Cancer Registry Data in Indonesia. (2021) - Gondhowiardjo, Soehartati; Christina, Nadia; Ganapati, Ngakan P.D.; Hawariy, Salik; Radityamurti, Fahmi; Jayalie, Vito F.; Octavianus, Steven; Prawira Putra, Andre; Sekarutami, Sri M.; Prajogi, Gregorius B.; Giselvania, Angela; Adham, Marlinda; et al.
Abstract : PURPOSE: In 2016, there were 1, 308, 061 cases of cancer being treated in Indonesia, with 2.2 trillion rupiahs spent, amounting to 486, 960, 633 in US dollars (purchasing power parity 2016). The high burden of cancers in Indonesia requires a valid data collection to inform future cancer-related policies. The purpose of this study is to report cancer epidemiological data from 2008 to 2012 based on Hospital-Based Cancer Registry (HBCR) data from Cipto Mangunkusumo Hospital, Indonesia. METHODS: This was a descriptive study with cross-sectional design. Data were collected from Cipto Mangunkusumo Hospital HBCR 2008-2012. Demographical, diagnostic, stages of cancer, and histopathological types of cancer data were extracted. RESULTS: After screening, 18, 216 cases were included. A total of 12, 438 patients were older than 39 years of age (68.3%), with a female-to-male ratio of 9:5. Most patients have cancers at advanced stages (stages III and IV, 10.2%). The most common sites of cancer were cervix uteri (2, 878 cases, 15.8%), breast (2, 459 cases, 13.5%), hematopoietic and reticuloendothelial systems (1, 422 cases, 7.8%), nasopharynx (1, 338 cases, 7.4%), and lymph nodes (1, 104 cases, 6.1%). CONCLUSION: From this HBCR, cancer incidence in female was almost twice the incidence in male, largely because of the burden of cervical and breast cancers. The cervix uteri as one of the top five cancer sites based on this HBCR, 2008-2012, are still approximately consistent with Global Cancer Incidence, Mortality and Prevalence 2018, which portrayed that Indonesia has been severely afflicted by cervical cancer cases more than any other Association of Southeast Asian Nations countries. The HBCR could serve as a robust database of epidemiological data for cancer cases in Indonesia.